Enactment of Third-Party Punishment by 4-Year-Olds - Kenward, Ben; Östh, Therese (Frontiers in Psychology, 2012)
When prompted, preschoolers advocate punishment for moral transgressions against third parties, but little is known about whether and how they might act out such punishment. In this study, adult demonstrators enacted doll stories in which a perpetrator child doll made an unprovoked attack on a victim child doll, after which an adult doll punished either the perpetrator (consistent punishment) or victim (inconsistent punishment). When asked to help retell the story, given free choice of their own preferred actions for the adult doll, four-year-olds (N = 32) were influenced by the demonstrated choice of target when selecting a target for punishment or admonishment. This influence was weak following inconsistent punishment, however, because the participants tended to change the story by punishing or admonishing the perpetrator when the demonstrator had punished the victim. Four-year-olds’ tendency to select a moral rule violator as a target for punishment is therefore stronger than their tendency to copy the specific actions of adults, which itself is known to be very strong. The evidence suggests that four-year-olds’ enactment of punishment is at least partially based on a belief that antisocial actions deserve to be punished.